Microfluidic Platforms for High-Throughput Pancreatic Ductal Adenocarcinoma Organoid Culture and Drug Screening - Geyer, Marlene; Queiroz, Karla (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic Ductal Adenocarcinoma (PDAC), the most common pancreatic cancer type, is believed to be the second leading cause of cancer-related deaths by 2030 with mortality rates of up to 93%. It is often detected at a late stage due to lacking symptoms, and therefore surgical removal of the tumor is the only hope for patients. Unfortunately, only 20% of the tumors are resectable, mainly due to early metastasis, which makes chemotherapeutic treatment the leading therapy for patients. PDAC is characterized by high-density stroma, thus inducing hypoxic conditions and high interstitial pressure. These factors impact carcinogenesis and progression of PDAC and support the formation of an immunosuppressive microenvironment that renders this tumor type refractory to immunotherapies. Most in vitro PDAC models have limited translational relevance, as these fail to recapitulate relevant aspects of PDAC complexity. Altogether, this highlights the urgent need for novel and innovative PDAC modeling platforms. Here, we discuss the relevance of microfluidic and organoid technologies as platforms for modeling bio- and physicochemical features of PDAC and as translational models that enable high-throughput phenotypic drug screenings, while also allowing for the development of novel personalized models used to identify treatment responsive patient subsets.